Analytic Methods for the Calculation of the Heat Transfer Coefficient - Merklein, Marion; Wieland, Michael; Stöhr, Thomas; Lechler, Jürgen; Grüner, Martin (International Review of Mechanical Engineering, 2010)
In the product development cycle numerical simulations are commonly used for the process layout. In case of hot stamping the process layout gets quite complex because material's thermal and mechanical properties have to be taken into account. Hot stamping can be explained as forming and quenching in one process step and therefore the knowledge of thermal properties is indispensable to fulfill the opposing requirements of a good heat flux with respect to a good energy balance of the tool. A description of this energy exchange between the hot blank and the tool is given by the heat transfer coefficient. The determination of the heat flux under process relevant conditions for hot stamping is influenced by several variables. Within the scope of this work, these different variables are compared using two analytical methods to calculate the heat transfer coefficient based on the same measurement data. Furthermore the advantage of these analytical methods and the possibility of improvement is shown up. At least a validation of the calculated heat transfer coefficients by simulation is presented. Copyright © 2010 Praise Worthy Prize S.r.l. - All rights reserved.
LFT Import::2019-07-29 (224)
Keywords: Heat transfer coefficient; Hot stamping